Emotional Memory in Post-traumatic Stress Disorder: A Systematic PRISMA Review of Controlled Studies - Durand, Florence; Isaac, Clémence; Januel, Dominique (Frontiers in Psychology, 2019)
BACKGROUND: Emotional memory is an adaptive process that improves the memorization of emotional events or stimuli. After being exposed to a traumatic event, as in Post-Traumatic Stress Disorder (PTSD), emotional memory may be altered. We performed a systematic review of the evidence of specific emotional memory in Post-Traumatic Stress Disorder patients. METHODS: Following PRISMA guidelines, a systematic review of MEDLINE, PsycInfo and ScienceDirect was undertaken to identify controlled studies on emotional memory that used cognitive tasks on PTSD patients. The initial research was conducted from June 2017 to July 2017, and search terms included: Post-Traumatic Stress Disorder; emotional memory; emotion; emotional; memory; and episodic memory. RESULTS: Fourteen studies reporting on 301 PTSD patients met the eligibility criteria. Among the studies selected, only six observed differences in emotional memory performance such as greater memorization of negative information, or a trend to false recognitions of negative information in PTSD. However, most other studies that did not find behavioral differences between PTSD and control groups showed specific cerebral activities, or differences in neurohormone levels, during emotional memory tasks. CONCLUSION: This review has several limitations, including a limited number of controlled studies, small samples, different tasks and methods. Consequently, we observed mixed results that provide interesting information on emotional memory in PTSD but needs further controlled studies with sensitive behavioral tasks. Also, future studies may evaluate emotional memory after symptom amelioration.